High genetic diversity of Enterococcus faecium and Enterococcus faecalis clinical isolates by pulsed-field gel electrophoresis and multi locus sequence typing from a hospital in Malaysia - Weng, Poh Leng; Ramli, Ramliza; Shamsudin, Mariana Nor; Cheah, Yoke Kqueen; Awang Hamat, Rukman (Hindawi Publishing Corporation, 2013)
Little is known on the genetic relatedness and potential dissemination of particular enterococcal clones in Malaysia. We studied the antibiotic susceptibility profiles of Enterococcus faecium and Enterococcus faecalis and subjected them to pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). E. faecium and E. faecalis displayed 27 and 30 pulsotypes, respectively, and 10 representative E. faecium and E. faecalis isolates (five each) yielded few different sequence types (STs): ST17 (2 isolates), ST78, ST203, and ST601 for E. faecium, and ST6, ST16, ST28, ST179, and ST399 for E. faecalis. Resistance to tazobactam-piperacillin and ampicillin amongst E. faecium isolates was highly observed as compared to E. faecalis isolates. All of the isolates were sensitive to vancomycin and teicoplanin. The presence of epidemic and nosocomial strains of selected E. faecium STs: 17, 78, and 203 and E. faecalis ST6 as well as high rates of resistance to multiple antibiotics amongst E. faecium isolates is of a particular concern.